EFEKTIFITAS MEDIASI DALAM MENYELESAIKAN SENGKETA PERCERAIAN (STUDY DI PENGADILAN AGAMA BUKITTINGGI DAN PENGADILAN AGAMA PAYAKUMBUH TAHUN 2015-2017) - Fauzi, Rahmat; Faisal, Faisal (Soumatera Law Review, 2018)
This research was conducted to reveal the Effectiveness of Mediation in Resolving Divorce Disputes in the Religious Courts. The purpose of this study is to describe the application and success rate of mediation in divorce cases in accordance with PERMA No.1 of 2016 concerning Mediation Procedures. As well as explaining the factors that are obstacles and driving the application of mediation as an effort to reduce the rate of divorce against divorce cases in the Religious Courts. So that the problems faced in the divorce dispute can be resolved through mediation by referring to PERMA No. 1 of 2016. This research will be conducted in the Bukittinggi Religious Court and Payakumbuh Religious Court, Case of 2015-2017. The approach used in this research is a sociological juridical approach which is a research based on a legal provision and a phenomenon or event that occurs in the field. The method used in analyzing data is using qualitative analysis methods. The conclusion of this study is the application of mediation in divorce cases in the Religion Court of the Bukittinggi Religion Court and the Payakumbuh Religious Court have not been effective because they are not in accordance with the intention of the issuance of the Supreme Court Regulation on Mediation Procedures in court. The success rate of mediation in the Bukittinggi Religious Court and Payakumbuh Religious Courts in 2015, 2016 and 2017 is very low, as evidenced by the number of cases that succeeded in mediating ± 5%. Supporting factors for the success of mediation: the ability of mediators, sociological and psychological, moral and spiritual factors and the good will of the parties. While the inhibiting factors for the success of mediation are as follows: the strong desire of the parties to divorce, prolonged conflict and economic factors.